Labor Migration and Social Networks Participation in Southern Mozambique (2013)
This paper investigates how social networks in poor developing settings are a?ected by migration. Using aunique household survey from southern Mozambique, we test the role of labour mobility in shaping partic-ipation in groups and interhousehold cooperation by migrant-sending households in village economies atorigin. We ?nd that migration cum remittances boosts household engagement in community-based socialnetworks. Our ?ndings are robust to alternative de?nitions of social interaction and to endogeneity con-cerns, suggesting that stable migration ties and higher income stability through remittances may decreaseparticipation constraints and increase household commitment in cooperative arrangements in migrant-sending communities